Revitalizing Moral Education to Overcome the Moral Crisis of Adolescents - Mariana (CV Edujavare Publishing, 2024)
The moral crisis among adolescents has become a serious social issue in contemporary society, characterized by increasing juvenile delinquency, violence, drug abuse, cyberbullying, promiscuity, disrespect toward parents and teachers, and declining ethical awareness. Rapid technological development, globalization, social media influence, weak family supervision, and declining moral education contribute significantly to changes in adolescent behavior and values. This study aims to analyze the importance of revitalizing moral education as an effort to overcome the moral crisis among adolescents and examine the role of families, schools, communities, and religious institutions in strengthening moral character development. The research employs a qualitative descriptive approach through literature review and contextual analysis of moral education, adolescent development, and contemporary social challenges. The findings indicate that moral education plays an essential role in shaping adolescents’ ethical awareness, self-control, empathy, responsibility, discipline, and social behavior. Effective moral education requires integration between cognitive understanding, emotional development, spiritual values, and practical moral habits within everyday life. The study also reveals that collaboration among parents, teachers, communities, and digital media literacy programs is necessary to address contemporary moral challenges affecting adolescents. Therefore, revitalizing moral education based on ethical, religious, and humanitarian values is essential for developing responsible, morally conscious, and socially constructive younger generations in modern society.